MODEL KOOPERATIF TIPE ROTATING TRIO EXCHANGE (RTE) DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS V SD NEGERI 1501 HURUNG JILOK - Hasibuan, Arfin; Rani Astria Silve; Harahap, Nurhalimah; Hasibuan, Annis (Yayasan Perguruan Kampus, 2025)
Based on the research results, it can be concluded that: (1) The mathematical concept understanding ability of students in the pre-cycle obtained a total score of 1330, with an average of 57.83, the highest score of 80 and the lowest score of 40. (2) The mathematical concept understanding ability of students in cycle I obtained a total score of 1710, an average of 74.35, the highest score of 90 and the lowest score of 50. The mathematical concept understanding ability of students in cycle II obtained a total score of 1930, an average of 83.91, the highest score of 90 and the lowest score of 60. The results of observations of the mathematical concept understanding of class V students at SD Negeri 1501 Hurung Jilok in cycle II have increased, namely there are only 20 students or 86.96% who understand the mathematical concept